Medical survey of female boxing in Italy in 2002–2003. Issue 8 (25th July 2005) - Bianco, M; Pannozzo, A; Fabbricatore, C; Sanna, N; Moscetti, M; Palmieri, V; Zeppilli, P
Abstract : Background: Female boxing has been permitted in Italy since 2001. According to the latest Italian laws, athletes applying to become boxers have to pass a pre-participation medical examination. Objective: To collect novel medical information from the pre-participation visits and mandatory pre-competition and post-competition examinations for all fights involving Italian female boxers in 2002–2003. Methods: A retrospective study on all official female boxing competitions in Italy from January 2002 to October 2003 was conducted. A prospective study on 28 amateur female boxers was also carried out. Results: Retrospective study: data from 664 examinations were collected. Pre-match examinations were negative. After competitions, 19/645 visits showed some injuries, with mild, soft tissue facial lesions, epistaxis, and hand-wrist problems being the most common. Prospective study: no major lesions were found during the study. One fibroadenoma, one ovarian cyst, and one intramural uterine myoma were found. One boxer was referred to a neurologist because of non-specific electroencephalographic (EEG) abnormalities, which persisted six months later. On a re-admission examination, which was needed because of a contest that was stopped because the referee judged that she was receiving blows to the head that were dangerous, one boxer showed non-specific EEG alterations and nystagmus. A cerebral magnetic resonance imaging scan was normal. She was allowed to participate in competitions again when her EEG returned to normal and clinical signs disappeared. Deviation of the nasal septum was quite common (68%). No major eye injuries were reported. Conclusion: Probably because of the correct preventive medical approach, female boxing is much safer than expected, and no major lesions (requiring hospital admission) were reported. Any lesions to the breast and reproductive system could not be considered to be boxing related.